2020
DOI: 10.3390/catal10030334
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of Co with Ni in Co/Al2O3 Catalysts for Fischer–Tropsch Synthesis

Abstract: The effect of cobalt substitution with nickel was investigated for the Fischer–Tropsch synthesis reaction. Catalysts having different Ni/Co ratios were prepared by aqueous incipient wetness co-impregnation, characterized, and tested using a continuously stirred tank reactor (CSTR) for more than 200 h. The addition of nickel did not significantly modify the morphological properties measured. XRD, STEM, and TPR-XANES results showed intimate contact between nickel and cobalt, strongly suggesting the formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…The nickel introduction method does not have a signifi cant effect, although peak 2 of Sample 4 is slightly shifted towards the high-temperature region. Similar regularities were also found in prior studies [52,53].…”
Section: Resultssupporting
confidence: 91%
“…The nickel introduction method does not have a signifi cant effect, although peak 2 of Sample 4 is slightly shifted towards the high-temperature region. Similar regularities were also found in prior studies [52,53].…”
Section: Resultssupporting
confidence: 91%
“…The use of a plasma, as well as microwave radiation with plasma generation, in catalyst preparation has also been used to enhance activity, selectivity, and long-term stability under service conditions. , These effects can be considered to be the result of structural surface heterogeneity induced in the supported catalyst due to the imposition of high energy density in a short-time span thus creating a nonequilibrium processing conditions with local temperatures reaching several thousand degrees . The chemical and morphological heterogeneity of several SiO 2 -supported catalysts prepared under combined plasma and microwave radiation has recently been characterized. , …”
Section: Introductionmentioning
confidence: 99%
“…A popular technique for FTS is based on so-called “flow chemistry” in which catalyst-coated microcapillary, monolithic, or foamed reactors are used . One of the advantages of this technique is that heat transfer can also be intensified by using cross-flow reactor configuration in which the reaction channels are separated from the heat-transfer channels by a thin section of highly conductive metal plates , The intensification of FT synthesis using the basic capillary, monolith, or foamed reactors can be further improved by reactor optimization , and through the enhancement of surface area density (surface area per unit volume) for heat and mass transfer in capillary/monolithic reactors and metallic foam reactors where the surface area density enhancement over 100 times is achieved compared with the commercially available foams.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of Martinelli et al [3] the effect of cobalt substitution with nickel was systematically investigated for the FTS. Catalysts with different Ni/Co ratios were prepared, characterized with various physicochemical techniques, and tested in a continuously stirred tank reactor for more than 200 h. The authors have found that substitution of Co with Ni did not significantly modify the morphological properties of the mixed catalyst.…”
mentioning
confidence: 99%